Constituents, Pharmacokinetics, and Pharmacology of Gegen-Qinlian Decoction - Lu, Jing-Ze; Ye, Dan; Ma, Bing-Liang (Frontiers in Pharmacology, 2021)
Gegen-Qinlian decoction (GQD) is a classic traditional Chinese medicine (TCM) formula. It is traditionally and clinically used to treat both the external and internal symptoms of diarrhea with fever. In this review, key words related to GQD were searched in the Web of Science, PubMed, China National Knowledge Infrastructure (CNKI), and other databases. Literature published mainly from 2000 to 2020 was screened and summarized. The main constituents of GQD could be classified into eight groups according to their structures: flavonoid C-glycosides, flavonoid O-glucuronides, benzylisoquinoline alkaloids, free flavonoids, flavonoid O-glycosides, coumarins, triterpenoid saponins, and others. The parent constituents of GQD that enter circulation mainly include puerarin and daidzein from Gegen, baicalin and wogonoside from Huangqin, berberine and magnoflorine from Huanglian, as well as glycyrrhetinic acid and glycyrrhizic acid from Gancao. GQD is effective against inflammatory intestinal diseases, including diarrhea, ulcerative colitis, and intestinal adverse reactions caused by chemotherapeutic agents. Moreover, GQD has significant effects on metabolic diseases, such as nonalcoholic fatty liver and type 2 diabetes. Furthermore, GQD can be used to treat lung injury. In brief, previous studies have elucidated the main active constituents of GQD and their interactions, and characterized the pharmacokinetic and pharmacological profiles of GQD. However, several issues of GQD, including effective constituents, interactions between the constituents, pharmacokinetics, potential herb–drug interactions of GQD, and pharmacological effects need further study. The findings of this review would improve readers’ understanding of the main constituents, pharmacokinetics, pharmacological effects, and action mechanism of GQD.